Study guides

☆☆

Q: What is the sum odd the odd integers from 1 to 139?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

The average of the two odd integers is 28. Therefore the two integers are 28-1 and 28+1, i.e 27 and 29.

Let's talk this out and see if we can work it out. The sum of the first N odd integers means, 1+3+5+7+9+11+... Where N is how many odd numbers we're adding. Let's choose numbers for N, and see if we can find a pattern. N=1 --> 1 (sum of the first odd integer) N=2 --> 1 + 3 = 4 (sum of the first 2 odd integers) N=3 --> 1 + 3 + 5 = 9 (sum of the first 3 odd integers) N=4 --> 1 + 3 + 5 + 7 = 16 Do you notice a pattern yet? Take a look at when N = 2, what is the sum? That's right, 4! and when N = 3... the sum is 9. N = 4 the sum is 16.... I see a pattern, do you? Answer: If you don't, you'll notice that the sum of the first N odd integers is always = N2

There are no such answers. The sum of even numbers is even. The sum of odd numbers could be even, but the sum of three consecutive odd numbers is always odd. One could swap the questions to get potentially answerable questions: Sum of 3 consecutive EVEN integers = 150 48 + 50 + 52 = 150 unfortunately, we can already see that if we were to make these odd integers (add 1 to each), we would get 153, not 151. Sum of 3 consecutive ODD integers = 151 49 + 51 + 53 = 153 47 + 49 + 51 = 147 We can see that, whenever we slide our three consecutive integers up one, we raise the value of the sum up 3, and if we jump from odd to odd, or even to even, we raise each integer by 2, so we raise the sum by 6.

(2x - 1) + (2x + 1) = 524x = 52x = 13The first 2 of 5 consecutive odd integers are 25 and 27.(Check: 25 + 27 = 52 yay!)The last 2 of 5 are 31 and 33.Their sum is 64.

The arithmetic sequence of odd integers is 1, 3, 5, 7, 9, ... where the common difference is 2. The sum of the first thirty odd integers can be found by using the sum formula such as: Sn = n/2[2a1 + (n - 1)d], where a1 = 1, n = 30, and d = 2. So, S30 = (30/2)[(2)(1) + (30 - 1)(2)] = (15)[2 + (29)(2)] = (15)(60) = 900

Related questions

The first odd positive integers are "1" and "3" which the sum is 4.

It is 2500.

The integers are -1, 1 and 3.

Divide the sum of the three consecutive odd integers by 3: -3 /3 = -1. The smallest of these integers will be two less than -1 and the largest will be two more than -1, so the three consecutive odd integers will be -3, -1, and +1.

-1, 1, 3, 5

The formula for the sum of the squares of odd integers from 1 to n is n(n + 1)(n + 2) ÷ 6. EXAMPLE : Sum of odd integer squares from 1 to 15 = 15 x 16 x 17 ÷ 6 = 680

The numbers are -3, -1, and 1.

The average of the two odd integers is 28. Therefore the two integers are 28-1 and 28+1, i.e 27 and 29.

-1, 1, 3, 5

Let's talk this out and see if we can work it out. The sum of the first N odd integers means, 1+3+5+7+9+11+... Where N is how many odd numbers we're adding. Let's choose numbers for N, and see if we can find a pattern. N=1 --> 1 (sum of the first odd integer) N=2 --> 1 + 3 = 4 (sum of the first 2 odd integers) N=3 --> 1 + 3 + 5 = 9 (sum of the first 3 odd integers) N=4 --> 1 + 3 + 5 + 7 = 16 Do you notice a pattern yet? Take a look at when N = 2, what is the sum? That's right, 4! and when N = 3... the sum is 9. N = 4 the sum is 16.... I see a pattern, do you? Answer: If you don't, you'll notice that the sum of the first N odd integers is always = N2

-1, 1, 3 -1 + 1 + 3 = 3

There are no such answers. The sum of even numbers is even. The sum of odd numbers could be even, but the sum of three consecutive odd numbers is always odd. One could swap the questions to get potentially answerable questions: Sum of 3 consecutive EVEN integers = 150 48 + 50 + 52 = 150 unfortunately, we can already see that if we were to make these odd integers (add 1 to each), we would get 153, not 151. Sum of 3 consecutive ODD integers = 151 49 + 51 + 53 = 153 47 + 49 + 51 = 147 We can see that, whenever we slide our three consecutive integers up one, we raise the value of the sum up 3, and if we jump from odd to odd, or even to even, we raise each integer by 2, so we raise the sum by 6.

People also asked